The Perspective of Contemporary Scholars on the Zakat Payment of YouTube Google AdSense Income - Syarif, Muhammad Fazlurrahman; Purwanti, Dewi; Akilah, Fahmiah (Universitas Islam Negeri Alauddin Makassar, 2022)
The potential of zakat through the Google Adsense business can be used as an instrument to encourage economic growth. This can be done regardless of the pros and cons among scholars against zakat payment on Google Adsense business income on youtube. Also, this article refers to a literature study with a normative and juridical approach. The results showed several scholars argued that even though the haul had not been achieved, professional or income zakat needs to be issued as long as the nishab had been reached. Some scholars also require professional or income zakat to be issued when the nishab and haul have been reached. Meanwhile, YouTubers and content creators are professionals who are loved by people of all ages and the job is promising in the millennial era with the potential to generate lots of zakat funds. It is hoped that more similar professions with great potential will emerge in the future. Therefore, people who earn from the Google Adsense business on youtube can better understand the payment of zakat from their income. This study can be a basis for further surveys on the development of other professional zakat.